2018
DOI: 10.18203/2394-6040.ijcmph20183047
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity is associated with lower blood glucose level in high school teachers in Palu, Indonesia

Abstract: Background: Physical activity refers to the movement of the body that causes the expenditure of energy for the maintenance of physical and mental health and is produced by skeletal muscle which is repeated over a period of time. The purpose of this research is to investigate the effect of physical activity on blood glucose level in high school teachers in Palu, Indonesia.Methods: This was a descriptive analytic research with a cross-sectional approach. The research was conducted in Palu city. Seventy-five pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
2
1
0
2
Order By: Relevance
“…The results of the bivariat analysis showed that there was a significant relationship between physical activity and fasting sugar levels in the study subjects (p = 0.023). This study is in line with research in Palu, Indonesia which states that high level of physical activity is effective in reducing sugar levels of high school teachers (Sakung et al, 2018). The increase of glucose use by the muscles will increase when a person performs heavy physical activity, because endogenous glucose keeps the balanced blood sugar levels.…”
Section: Discussionsupporting
confidence: 88%
“…The results of the bivariat analysis showed that there was a significant relationship between physical activity and fasting sugar levels in the study subjects (p = 0.023). This study is in line with research in Palu, Indonesia which states that high level of physical activity is effective in reducing sugar levels of high school teachers (Sakung et al, 2018). The increase of glucose use by the muscles will increase when a person performs heavy physical activity, because endogenous glucose keeps the balanced blood sugar levels.…”
Section: Discussionsupporting
confidence: 88%
“…The association between PA level and non-fasting blood glucose level (NFBG) was not seen in this study. Previous study has shown a significant positive asociation between PA level and blood glucose among adult in Malaysia (10) which is consistent with other research reports which showed an association between higher activity level and lower level of blood glucose (23,24). These differences in findings between our study and other studies might due to the characteristic of subjects.…”
Section: Discussionsupporting
confidence: 87%
“…Studi yang telah dilakukan pada 75 guru SMA di Kota Palu didapati terdapat hubungan antara tingkat aktivitas fisik dengan kadar glukosa darah (Sakung et al, 2018). Tingkat aktivitas yang rendah berhubungan dengan kadar glukosa darah abnormal bahkan pada berat badan yang sehat (Mainous et al, 2017) Uraian ini menjadi alasan peneliti tertarik untuk melakukan penelitian yang bertujuan untuk mengetahui hubungan aktivitas fisik dengan kadar glukosa darah puasa pada wanita dengan lingkar pinggang diatas 80 cm pada mahasiswi di Universitas Advent Indonesia.…”
Section: Research Articleunclassified